2017
DOI: 10.1186/s13063-017-1962-z
|View full text |Cite
|
Sign up to set email alerts
|

Developing and evaluating multimedia information resources to improve engagement of children, adolescents, and their parents with trials (TRECA study): Study protocol for a series of linked randomised controlled trials

Abstract: BackgroundRandomised controlled trials are widely established as the best method for testing health interventions whilst minimising bias. However, recruitment and subsequent retention of children and adolescents in healthcare trials is challenging. Participant information sheets are often lengthy and difficult to read and understand. Presenting key information using multimedia may help to overcome these limitations and better support young people and their parents in deciding whether to participate in a clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 57 publications
(80 reference statements)
0
26
0
Order By: Relevance
“…However, these documents have been criticized for being too long and complex (Caldwell et al, 2012;Tarnowski et al, 1990), and digital resources may be a promising alternative. The TRECA study, which consists of two phases, aims to develop and evaluate the use of digital, multimedia information resources (MMIs) provided to children, young people and their families when they are invited to take part in a health-care trial (Martin-Kerry et al, 2017). In Phase 1, prototype MMIs containing text, animations, video and pictures were developed with input from study participants including children, young people, families and health-care professionals, to ensure they met people's needs and preferences .…”
Section: The Treca Studymentioning
confidence: 99%
See 1 more Smart Citation
“…However, these documents have been criticized for being too long and complex (Caldwell et al, 2012;Tarnowski et al, 1990), and digital resources may be a promising alternative. The TRECA study, which consists of two phases, aims to develop and evaluate the use of digital, multimedia information resources (MMIs) provided to children, young people and their families when they are invited to take part in a health-care trial (Martin-Kerry et al, 2017). In Phase 1, prototype MMIs containing text, animations, video and pictures were developed with input from study participants including children, young people, families and health-care professionals, to ensure they met people's needs and preferences .…”
Section: The Treca Studymentioning
confidence: 99%
“…The impact of the MMIs will be assessed against three outcomes: (1) trial recruitment rates; (2) trial retention rates; and (3) the quality of decision-making by potential trial participants and (where relevant) their parents. Further information about the TRECA study is available in the published protocol (Martin-Kerry et al, 2017).…”
Section: The Treca Studymentioning
confidence: 99%
“…The Thermic-3 trial is embedding the Trials Engagement in Children and Adolescents (TRECA) SWAT. 13 This SWAT is investigating a novel method for recruitment to see whether providing children and their families with information about a trial through multimedia information (MMI) resources impacts on recruitment and retention rates and the quality of decision-making about trial participation. The MMI resources are websites with text, images, animations and videos about the Thermic-3 trial.…”
Section: Embedded Treca Study Within a Trial (Swat)mentioning
confidence: 99%
“…Prior to approach about the Thermic-3 trial, potential patients will be randomised (1:1:1) to one of the three TRECA SWAT groups: patient information leaflet (PIL), MMI or both PIL and MMI. 13 Parents/ guardians will be given either a PIL, MMI or both PIL and MMI. Patients aged over 7 years old will also be provided with a PIL, MMI or both PIL and MMI suitable to their age group (7-10 years, 11-15 years or 16 years and over).…”
Section: Patient Approach and Consentmentioning
confidence: 99%
“…Although focused on decision making for participation in healthcare trials involving CYP (the benefits and burden of participation are likely to differ for non-trial studies), a current trial is underway to evaluate how multimedia interventions, including textual, audio and visual information compare with written information. 32 The involvement of clinicians from the study design stage was viewed as important by CIs and should be considered a priority in future guidance. Taking a participatory approach to research, with health professionals involved early on, has been shown to be effective in prior palliative care research, 33 both in terms of the representativeness of the sample and positive perspective of health professionals when collecting the data.…”
Section: What Is Already Known About This Topic and What This Researcmentioning
confidence: 99%